Outcome of One and Two Visit Root Canal Treatment of Irreversible Pulpitis (Ibrahim Cardiac Medical Journal, 2017)
Objective: The present prospective comparative clinical trial was undertaken to compare the outcomes of single and two-visit root canal treatment of irreversible pulpitis.Methodology: This prospective study was conducted in the Department of Conservative Dentistry and Endodontics of Dhaka Dental College on patients who presented with pain due to irreversible pulpitis. Patients with single-rooted teeth with uncomplicated canal and full-formed apex having irreversible pulpitis were included. However, pregnant women or patients under treatment of antibiotics, cortiosteiods or suffering from any systemic diseases or immuno-compromised patients or patients having teeth with calcified canal or periodontal disease were excluded. A total of 80 patients who met the eligibility criteria were consecutively included and were randomly assigned to either one-visit (n = 40) or two-visit (n = 40) treatment groups. Data were kept on pulp vitality status, the presence or absence of pre-operative pain and degree of post obturation pain at 6, 12, 24, 48 hours and 1 week postoperatively. The outcome variable was intensity of pain which was measured using a visual analogue scale (VAS) as 0 = no pain, 1 = slight pain or discomfort, 2 = moderate pain relieved by analgesic, 3 = moderate to severe pain not completely relieved by analgesics and 4 = severe pain or swelling not relieved by analgesics and required unscheduled visit.Result: Forty percent of the patients in the two-visit group did not have any pain (measured in terms of visual analogue scale) at 12 hours compared to 25% in the single visit group, although the difference did not turn significant (p = 0.580). Likewise the proportion of patients without pain in the two-visit group was considerably higher (52.5%) at 24 hours than that in the single-visit group (45%) (p = 0.852). Improvement in pain sensation was reported to be significantly higher in the two-visit group (as 95% of the patients did not complain any pain) at 48 hours than that in the single-visit group (80% of the patients did not complain any pain) (p = 0.015). None of the patients of either group complained of pain one week postoperatively.Conclusion: Compared to single-visit, two-visit root canal treatment showed better results in terms of intensity of post-obturation pain at 12, 24 and 48 hours after root canal treatment for irreversible pulpitis.Ibrahim Card Med J 2015; 5 (1&2): 45-48